ANALISIS YURIDIS KESULITAN AHLI WARIS MELAKUKAN KLAIM ASURANSI JIWA DEBITUR YANG MENINGGAL DUNIA DISEBABKAN COVID-19 (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2023)
Life insurance is a form of self-protection for the future when something unexpected happens. Based on the law, credit can also fall on heirs if the debtor dies before paying off the remaining credit. However, the Covid-19 period is often used as an excuse by insurers as a form of disease, not an epidemic. This is what makes the heirs unable to claim the insurance. This study aims to analyze the legal consequences of credit agreements for debtors who have died as a result of Covid-19. This study uses normative research methods with constitution and conceptual approaches. The results of the study show that the legal consequences of the credit agreement in the event that the debtor dies there are 2 possibilities, namely: the credit goes to the heirs as stipulated in Article 833 of the Civil Code (Burgerlijk Wetboek) or the guarantee is executed by the leasing party, and the second possibility is the credit is written off due to a life insurance clause or life insurance agreement. This means that here the insurer must be responsible for paying off the remaining debts of the debtor who died according to the terms and conditions in the policy, otherwise the interested party can submit a subpoena to sue the insurer. Because considering that Covid-19 is an epidemic/pandemic that was never predicted and thought about, it is not a disease that has long existed in the debtor's body. From this, it can be concluded that the parties must fully understand the contents of the credit agreement made, so that later if this risk occurs, the insurance can be disbursed. Keywords: Insurance; Debtor; Heir; Covid-19; Agreement;